Vascularized Bone Grafting in the Treatment of Scaphoid Nonunion: A Clinical and Functional Outcome Study - (:unkn) unknown (THIEME MEDICAL PUBL INC, 2022)
Background A malreduction or missed scaphoid fracture may lead to nonunion or avascular necrosis (AVN). The aim of this study was to analyze the radiological and clinical outcome of patients with scaphoid nonunion (SN), who were treated with 1,2-intercompartmental supraretinacular artery pedicled vascularized bone graft (1,2-ICSRA-VBG) fixed with K-wires or screws between 2014 and 2018. Methods Radiological assessment included posteroanterior, lateral, oblique, and angled posteroanterior projection. The wrist active joint range of motion was assessed with a universal goniometer, and grip and pinch strength with a dynamometer. The disabilities of the arm, shoulder and hand (DASH) questionnaire was used to evaluate functionality. Statistical analysis was performed using SPSS software (v16.0). Results A total of 68 patients (65 male) with a mean age 29.7 +/- 8.5 years were evaluated in the study, and union was achieved in 55 (81%). A total of 45 (66%) patients had scaphoid waist fracture and 48 (71%) had AVN. Fixation was achieved with K- wires in 48 of the patients, and with screw in 20. The mean length of follow-up was 31.6 +/- 14.6 (12-72) months. The mean radioulnar range of motion and DASH scores improved significantly after treatment (p< 0.001, p <= 0.001). Conclusions The findings of this study showed that scaphoid unions can be treated successfully with high rates of union using the 1,2-ICSRA-VBG. This surgical technique requires special surgical experience. The functional outcome of patients improved after treatment, although smoking was found to be an important factor affecting functional results.
Keywords: avascular necrosis; nonunion; scaphoid; vascular bone grafting; wrist; SUPRARETINACULAR ARTERY; DISTAL RADIUS; MANAGEMENT; FRACTURES; DIAGNOSIS